Efektifitas Strategi Pembelajaran Kooperatif dan Problem Posing dengan Kombinasi tutorial Online untuk Meningkatkan Pemahaman Materi Mata Kuliah Fisika Dasar - Sulistyaning Kartikawati (Jurnal Pendidikan, 2010)
This research is attempted to identify the effectiveness of cooperative learning and problem posing with on-line tutorials to increase students’ achievement in Basic Physics subject, students’ cooperative skill in posing problems, students’ cooperative skill in inputing problems under computer’s software, students’ thinking process and their attitudes against the implementation of problem posing atrategy with on-line tutorials under cooperative method. This research is carried out at STT Dharma Ishwara Madiun. The Subjects of the research are semester IB students of Basic Physics subject. The research is focused on the effectiveness of learning process which is indicated by the progress of students’ achievement, problem posing skill, problem input skill under computer’s software and attitude against the learning process. The research is designed in two-cyle collaborative learning technique based on problems arising in Basic Physics class. Instruments applied to obtain data are achievement test, problem posing test, students questionnaire and interview protocol. The results of analusis show that: 1) students’ achievement make a progress in cycle 1 to cycle 2, also the average students’ score. Progress shows: from 3 to 6 students wighing above 75of score; 7 to 15 students wighing 60-75 of score; good cooperative skill from 8 to 10 groups; thinking process develops through the flow understanding the command putting practice in the doing task under computer’s software.